Planning a Micro-Hydro System for Irrigation and Agricultural Electrification in Campaga Village, Tompobulu District - Wahdaniah Hamzah; Mahmud Achmad; Abdul Azis; Daniel Useng; Haerani Haerani; Syahrial Sabaniah (Salaga Journal, 2025)
Dependence on fossil fuels and limited access to electricity and clean water are challenges to agricultural productivity in many rural areas of Indonesia, including Campaga Village. This study aims to plan an appropriate water energy conversion (pico-hydro) system to meet the operational energy needs of agriculture, particularly irrigation pumps and lighting. The planning began with measuring the potential of resources (discharge, head) and analyzing energy needs based on agricultural applications. The measurement results showed an average discharge of 0.134 m³/s with an effective head of 10.5 m, with the potential to generate mechanical power for pumps of 3.9 kW and electrical power of 2.2 kW. The needs analysis confirmed that this potential is more than sufficient to power one irrigation pump unit (~3 kW) and light 21 road lighting points (0.63 kW). The technical planning recommends the use of a crossflow turbine and a standard AC generator in accordance with the principles of appropriate technology: simple, locally maintainable, and directly integrated with agricultural needs. The conclusion of this study shows that the designed pico-hydro system is not only technically feasible but also has the potential to become strategic supporting infrastructure to improve irrigation water resilience, extend farming hours, and ultimately empower the economy of agrarian rural communities.